The looming Central and Eastern European real convergence club: Do implicit tax rates play a part? - Liliana E. Donath; Petru-Ovidiu Mura (DANUBE: Law, Economics and Social Issues Review, 2019)
The paper investigates whether there is a convergence club stance for theVisegrad countries plus Romania and Bulgaria and the part played, in this process, by the implicit tax rates on labour and consumption, respectively. For the purpose of the research, the GDP per capita, productivity and unemployment are used as convergence indicators and dependent variables. The dataset covers the 1995-2016 timeframe and the analysis is based on a panel-model approach. The main results show that the implicit tax on labour has no significant effect on the convergence indicators while the implicit rates on consumption are statistically significant with negative influence. The interpretation of results is made considering a set of control and robustness variables where policy lessons derive from. The conclusion reflects on the policy lessons that can serve to accomplish the convergence club within selected CEE countries: Bulgaria, the Czech Republic, Hungary, Poland, Slovakia and Romania.
Keywords: 330; Convergence Club; Implicit Tax Rate on Labour; Implicit Tax Rate on Consumption; CEE Countries; Real Indicators